Theory of Harm and Damages in the Pre-Soviet Period of Civil Law Development - A. Vlasov, Anatoliy; N. Koval, Vladimir; E. Monastyrskiy, Yuriy (International Journal of Engineering and Technology, 2018)
The works of the first Russian jurists on the issues of damages in civil law are insufficiently used in science. This article may fill the gaps and be interesting for professionals in the field of studies. Historical and comparative methods were used when reading and comparing all pre-Revolutionary works on the topic. It was found that the science of civil law abstracted from universal adjudication of damages reimbursement as a means of legal protection and focused on its interpretation as a sanction for offence. The modern authors repeat the four-level structure of cases on damages, adopted and elaborated in the Soviet period: illegality, causality, guilt, and proved decrease of property. The authors conclude that it is necessary to return to pre-Revolutionary conceptions and use them for improving the current theory of damages.Â Â